Rock and rock mass characterization for deep mining using sonic data - Valley, Benoît; Bewick, R. P; Hudson, R. (My University, 2011)
Rock and rock mass strength characterization is critical for the planning of deep mass mining projects where large capital investments are needed before extraction can begin. The deep nature of such projects also impliesthat initial data are gathered mostly in and from boreholes, and that core samples can be damaged by high relative stress conditions at the sampling point. In these conditions, it would be advantageous to use wirelogs, like full waveform sonic logs, to assess in situ rock strength and rock mass quality. This paper presents the processing methods that need to be applied to such logs in order to extract relevant sonic parameters and results from correlations between these parameters and rock properties. Literature review as well as the results presented in this paper show that a correlation exists between intact rock strength and p-wave velocity, but large scatter is present when the velocity exceeds about 3.5 km/s. However, sonic velocity is shown to be useful in identifying the occurrence of core damage and potential strength or stress anomalies. The impact of the fracturing level on the sonic response is also studied and is shown to result in increasing attenuation and frequency shift with increases in fracture intensity.